How Teaching Affects Student Attitudes towards the Environment and Sustainability in Higher Education: An Instructors’ Perspective - Misseyanni, Anastasia; Marouli, Christina; Papadopoulou, Paraskevi (European Journal of Sustainable Development, 2020)
In the rapidly changing, 21st century globalized world, with increasing environmental pressures and challenges, education for the environment and sustainability is a priority at all levels; from kindergarten to higher education. It is the education that will create the environmentally aware and socially responsible individuals, capable of addressing existing and future environmental challenges. Courses on the environment and/or sustainability are now an essential element of all Higher Education Institutions with a sustainability vision. But, does teaching about the environment and sustainability lead to a change in student attitudes? What teaching and learning methods seem to have a more significant effect on attitudes and behaviors and what are the challenges for instructors? In this study, instructors reflect on which educational methods seem most effective in promoting change in student attitudes and behaviors towards the environment and sustainability. This reflection is based on instructor experiences from selected courses or course activities (learning objects) and it focuses on the goals, teaching methods and effect on student learning and attitudes; changes in student attitudes in the course of the last years are also discussed. Suggestions are offered and implications for higher education institutions are outlined. Keywords: education for the environment, education for sustainability, higher education, active learning, student behaviors, emotional engagement